Imaging Chemical Kinetics of Radical Polymerization with an Ultrafast Coherent Raman Microscope - Haozheng Li; Yong Cheng; Huajun Tang; Yali Bi; Yage Chen; Guang Yang; Shoujing Guo; Sidan Tian; Jiangshan Liao; Xiaohua Lv; Shaoqun Zeng; Mingqiang Zhu; et al. (Advanced Science, 2020)
Abstract Numerous mechanisms have been proposed for polymerization to provide qualitative and quantitative prediction of how monomers spatially and temporally arrange into the polymeric chains. However, less is known about this process at the molecular level because the ultrafast chemical reaction is inaccessible for any form of microscope so far. Here, to address this unmet challenge, a stimulated Raman scattering microscope based on collinear multiple beams (COMB‐SRS) is demonstrated, which allows label‐free molecular imaging of polymer synthesis in action at speed of 2000 frames per second. The field of view of the developed 2 kHz SRS microscope is 30 × 28 µm2 with 50 × 46 pixels and 7 µs dwell time. By catching up the speed of chemical reaction, COMB‐SRS is able to quantitatively visualize the ultrafast dynamics of molecular vibrations with submicron spatial resolution and sub‐millisecond temporal resolution. The propagating polymer waves driven by reaction rate and persistent UV initiation are observed in situ. This methodology is expected to permit the development of novel functional polymers, controllable photoresists, 3D printing, and other new polymerization technologies.